Positional enhancement in effortbased social comparisons - Jeroen Nieboer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
Salient social comparisons to peers are generally thought to increase people's productive effort. But social comparisons can also become ends in themselves, with individuals seeking to outrank others by costly, non-productive means. This paper explores the motives behind such tendencies in the context of a real-effort task. We offer subjects the option of enhancing their relative position, at a cost to themselves, in a social comparison based on points earned on the task. Despite receiving no tangible benefits from enhancing their position, at least half of our subjects sacrifice some of their experimental earnings to do so. We find that information conditions are crucial: expenditure on positional enhancement is twice as high when social comparisons only occur after enhancement. Surprisingly, this effect is not driven by the visibility of subjects' positional enhancement to peers; the increase is due to ex ante uncertainty over how one's (unenhanced) task output compares to peers. Since many professional settings are characterized by uncertainty over peer output, these findings can help organizations identify positional enhancement and reduce its costs.
Keywords: 330; Social comparison; Status; Competition; Experiment